Brain computer interface based applications for training and rehabilitation of students with neurodevelopmental disorders. A literature review. Issue 9 (September 2020) - Papanastasiou, George; Drigas, Athanasios; Skianis, Charalabos; Lytras, Miltiadis
Abstract: The aim of this article is to explore a paradigm shift on Brain Computer Interface (BCI) research, as well as on intervention best practices for training and rehabilitation of students with neurodevelopmental disorders. Recent studies indicate that BCI devices have positive impact on students' attention skills and working memory as well as on other skills, such as visuospatial, social, imaginative and emotional abilities. BCI applications aim to emulate humans' brain and address the appropriate understanding for each student's neurodevelopmental disorders. Studies conducted to provide knowledge about BCI-based intervention applications regarding memory, attention, visuospatial, learning, collaboration, and communication, social, creative and emotional skills are highlighted. Only non-invasive BCI type of applications are being investigated based upon representative, non-exhaustive and state-of-the-art studies within the field. This article examines the progress of BCI research so far, while different BCI paradigms are investigated. BCI-based applications could successfully regulate students' cognitive abilities when used for their training and rehabilitation. Future directions to investigate BCI-based applications for training and rehabilitation of students with neurodevelopmental disorders concerning the different populations involved are discussed. Abstract : Education; Neuroscience; Psychology; Evaluation in education; Evidence-based education; Health education; Pedagogy; Teaching research; Brain computer interface; Rehabilitation; Cognitive disabilities; Intervention; Neurofeedback; Neurodevelopmental disorders; BCI; EEG